2015
DOI: 10.2105/ajph.2013.301859
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Brief Intervention, and Referral to Treatment for Older Adults With Substance Misuse

Abstract: Objectives. We compared substance use and SBIRT (Screening, Brief Intervention, and Referral to Treatment) services received for older adults screened by the Florida BRITE (BRief Intervention and Treatment of Elders) Project, across 4 categories of service providers. Methods. Staff from 29 agencies screened for substance use risk in 75 sites across 18 Florida counties. Clients at no or low risk received feedback about screening; moderate risk led to brief intervention, moderate or high risk led to brief treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…In this sense, national 2,11,14,16 and international 20,[22][23] authors have pointed out the efficacy of this model of brief intervention performed by professionals working in primary health care. Therefore, the present study emphasizes the importance of the qualification of the health professionals that develop their activities in primary health care in the FHS in order to provide a better service to people with problems related to alcohol and other drugs welcomed at the health system gateway.…”
Section: 14-15mentioning
confidence: 98%
“…In this sense, national 2,11,14,16 and international 20,[22][23] authors have pointed out the efficacy of this model of brief intervention performed by professionals working in primary health care. Therefore, the present study emphasizes the importance of the qualification of the health professionals that develop their activities in primary health care in the FHS in order to provide a better service to people with problems related to alcohol and other drugs welcomed at the health system gateway.…”
Section: 14-15mentioning
confidence: 98%
“…Results suggest that hazardous use of alcohol (15.4%) is higher among respondents from The Villages than in studies of community‐dwelling elders (about 9%) (Merrick et al , ; Schonfeld et al , ), but slightly less than reported in one other study of retirement communities (Alexander and Duff, ). The negative correlation between alcohol consumption and depressive symptoms also suggests that higher levels of consumption are driven by something else.…”
Section: Discussionmentioning
confidence: 97%
“…Future intervention and policy research is needed to determine whether various changes (e.g., professionals’ training, reimbursement policies, delivery methods such as telehealth and integration into medical and social service settings) will actually improve access. It is likely that the engagement of multiple stakeholders, including state policymakers, will be key to improving psychotherapy access for depression—as it was for improving behavioral intervention access for older adults with substance misuse (Schonfeld et al in press, 2010; Schonfeld and Hedgecock 2008). Policymakers in state legislature and state agencies (such as state units on aging, mental health, and substance abuse) could work together to develop protocols and pool resources for training, implementation, and evaluation at multiple provider agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from outreach and screening efforts in six counties of Florida by partnering with the Florida BRITE Project (Schonfeld et al in press, 2010). BRITE is a statewide program of community outreach, screening, and brief interventions.…”
Section: Methodsmentioning
confidence: 99%